Integrins are Mechanosensors that Modulate Human Eosinophil Activation - Ahmadzai, Mohammad Mustafa (My University, 2014)
Eosinophils are end-point effectors of inflammation that contribute to the clinical severity of asthma. Eosinophil homing to the asthmatic lung is primarily guided by eotaxin-1, which is an eosinophil-selective chemokine. The mechanism by which eotaxin-1 augments intracellular calcium during cell migration is incompletely understood but is integral to the extravasation of eosinophils at sites of inflammation. We consequently report here that fluid shear stress, like eotaxin-1, unexpectedly activates human eosinophils in a calcium-dependent manner. We used confocal fluorescence microscopy to study calcium-handling in purified human eosinophils. Application of eotaxin-1 augmented the [Ca2+]i in a concentration-dependent manner. Pre-treatment of cells with ryanodine (10 μM) completely abolished the eotaxin-mediated calcium response, indicating that this phenomenon is dependent on Ca2+-release from the ER. Several SOCC blockers (2-APB, 100 μM; Gd3+, 10 μM; SKF-96365, 100 μM) attenuated SOCE, suggesting that these channels may directly contribute towards the eotaxin-1 calcium response in human eosinophils. In the presence of fluid-perfusion, eosinophils displayed a robust perfusion-induced calcium response (PICR) demonstrating that eosinophils are mechanically sensitive. The PICR rapidly induced adhesion and non-directional migration in eosinophils, suggesting that some hitherto unknown molecular mechanosensor permits these cells to detect and respond to changes in shear-stress. Pre-treatment of eosinophils with the non-selective tripeptide integrin receptor blocker, Arg-Gly-Asp (RGD), abrogated the PICR. The highly selective, dual α4β7/α4β1 integrin receptor blocker, CDP-323, was used to ascertain whether these highly expressed integrin subtypes mediate the PICR in eosinophils. Pre-treatment of cells with CDP-323 completely abolished the PICR, in addition to the eotaxin-mediated calcium response in a shear-dependent manner. Taken together, our results support a novel role for the α4β7/α4β1 integrin receptors as mechanosensors that directly modulate [Ca2+]i, adhesion and migration in human eosinophils. On-going experiments will seek to quantify the shear-response thresholds at which eosinophils activate and the time-course of the associated calcium response. This study suggests that the recruitment and activation of eosinophils are regulated by chemical and mechanical stimuli via overlapping, calcium-dependent signal transduction cascades. Given that the PICR is mediated by the eosinophil-specific α4β7/α4β1 integrin receptors, we conclude that integrin receptors are molecular mechanosensors that may facilitate eosinophil activation, adhesion and non-directional migration independently of, or in conjunction with, chemokine signaling.
Keywords: Eosinophils; Intracellular Calcium; Integrins; Mechanosensitive; Inflammation; Asthma